The effect of education on marital status and partner characteristics: Evidence from the UK - Dan Anderberg; Yu Zhu (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper uses a particular school exit rule previously in effect in England and Wales that allowed students born within the first five months of the academic year to leave school one term earlier than those born later in the year. Focusing on women, we show that those who were required to stay on an extra term more frequently hold some academic qualification. Using having been required to stay on as an exogenous factor affecting academic attainment, we find that holding a (low level) academic qualification has no effect on a women's probability of being married, but increases the probability of her husband holding some academic qualification and being economically active.
Keywords: I10; J12; 330; education; marriage; assortative mating; Bildungsabschluss; Ehe; Geschlecht; Akademische Berufe; Schätzung; Großbritannien